Utilização da matriz dérmica acelular exposta em sítios de extração dentária - Silva, Sérgio Rodrigo Ribeiro da (2006)
The use of biomaterials in extraction sites has been dissiminated among dental practioners. The maintenance of the ridge, iniciated immediately after the extraction, is the simplest way to avoid future complications related to the absence or reduced volume of bone in the residual ridge. Biological membranes are biomaterials that can me used in order to isolate the socket from the adjacent soft tissue, allowing the migration of osteogenic cells. The objective of the study was to evaluate the clinical progression of the membrane and soft tissue when an Acellular Dermal Matrix (ADM) is utilized in extraction sites and left partially exposed to the bucal environment. Fifteen patients were submitted to extractions of lower bicuspids and their sockets covered with ADM. The ADM was left exposed during the whole healing and new tissue formation process. Clinical observations and mensurations were weekly done until the membrane was no longer identifiable. No patient presented adverse inflammatory or infection reactions. The final result, observed after 90 days, demonstrated a clinical increase of approximately 109% of queratinized gingiva. The histologic analisis of the tissue, from the area where the ADM was left exposed, revealed a similar aspect to a normal queratined gingiva, but with a larger amount of fibers present.